2021
DOI: 10.1039/d1md00202c
|View full text |Cite
|
Sign up to set email alerts
|

A novel compound active against SARS-CoV-2 targeting uridylate-specific endoribonuclease (NendoU/NSP15): in silico and in vitro investigations

Abstract: NendoU (NSP15) is an Mn(2+)-dependent, uridylate-specific enzyme, which leaves 2'-3'-cyclic phosphates 5' to the cleaved bond. Our in-house library was subjected to high throughput virtual screening (HTVS) to identify compounds...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…19 Recently, several HEA analogs have been reported as efficacious against the SARS-CoV-2 virus. 20–22 FDA-approved protease inhibitors of HIV 18 also support the importance of the HEA pharmacophore (Fig. 1).…”
Section: Introductionmentioning
confidence: 78%
“…19 Recently, several HEA analogs have been reported as efficacious against the SARS-CoV-2 virus. 20–22 FDA-approved protease inhibitors of HIV 18 also support the importance of the HEA pharmacophore (Fig. 1).…”
Section: Introductionmentioning
confidence: 78%
“…As shown above, all five compounds that we found by GLIDE are nucleotide analogues as well. Very recently, Kumar et al carried out in silico and in vitro screening for active compounds from their in-house libraries targeting to Nsp15 and identified ‘Compound IV’ ((2S,3S)-3-amino-1-(4-(4-(tert-butyl)benzyl)piperazin-1-yl)-4-phenylbutan-2-ol) as the best one in in vitro assays 37 . Of these, functional groups of Compound IV share analogous interactions with Nsp15 in Pocket A/B with those of the compound of pose 4 that shows the lowest .…”
Section: Resultsmentioning
confidence: 99%
“…Another recent study identified additional FDA‐approved drugs that can inhibit Nsp15 activity in vitro [ 86 ]. Using high‐resolution structures as the starting point, in silico screening approaches have also identified numerous putative Nsp15 inhibitors [ 87 , 88 , 89 , 90 , 91 , 92 ].…”
Section: Inhibitors Of Nsp14 and Nsp15mentioning
confidence: 99%